Vascularization in 3D tissue using cell sheet technology. (May 2013) - Sekiya, Sachiko; Shimizu, Tatsuya; Okano, Teruo
Tissue engineering is a field of study unto itself, but in reality, it is a fusion of medicine, pharmacology, chemistry, cell biology, molecular biology and engineering. The field has been developing at an ever-increasing pace and already provides benefits to regenerative medicine in areas such as the skin and cornea. However, the problem facing all of these technologies is the diffusion limitation, which has impeded the fabrication of thicker 3D tissue. Overcoming this problem requires vascularization of 3D tissue, which is critical to any future advances. Here, we introduce our own cell sheet technology and compare it with other technologies for the fabrication of vascularized 3D tissue.